EFEKTIVITAS PENEGAKAN HUKUM PIDANA (STUDI TERHADAP PENEGAKAN HUKUM KASUS PEMBUATAN PUPUK OPLOSAN/PALSU YANG DILAKUKAN OLEH CV. INDO AGRITAMA INDUSTRI JEPARA) - Ikwan Daldiri Budi Santosa; Akhmad Khisni (UNISSULA Semarang, 2017)
The legal system can be said to be effective when human behavior in society is in accordance with what has been determined in the applicable legal rules. Law enforcement in principle should be able to provide assurance of legal certainty and useful for the community, in addition the community also expect law enforcement to achieve a justice. Law enforcement officers must be able to escape from the culture of the existing legal apparatus has been considered unfair and changed towards the improvement of human resources, better management becomes an asset to be perform the duties of the ideal law enforcement officers. The legal culture of a good law enforcement apparatus will result in effective and efficient law enforcement.Keywords: Effective And Efficient Law Enforcement